2015
DOI: 10.1177/0272431615596427
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assets and Risky Sexual Behaviors Among American Indian Youth

Abstract: This study examined the relationship between developmental assets during early and mid-adolescence and early adult sexual behaviors among American Indians using a subsample from the National Longitudinal Study of Adolescent Health ( = 465). Grounded in an assets framework, the authors explored the protective role of personal, family, school, and community assets as well as cumulative assets for sexual behaviors including early sexual debut, number of sexual partners, and frequency of condom use. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…The finding that external assets are associated with positive identity is in line with the extant literature showing positive associations among the assets, and between the assets and positive outcomes, such as academic success psychological wellbeing ( Jain et al, 2012 ; Scales et al, 2017 ; Greene et al, 2018 ; Adams et al, 2019 ; Kaur et al, 2019 ; Soares et al, 2019 ). In view of this literature, the positive association between external assets and positive identity was expected.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding that external assets are associated with positive identity is in line with the extant literature showing positive associations among the assets, and between the assets and positive outcomes, such as academic success psychological wellbeing ( Jain et al, 2012 ; Scales et al, 2017 ; Greene et al, 2018 ; Adams et al, 2019 ; Kaur et al, 2019 ; Soares et al, 2019 ). In view of this literature, the positive association between external assets and positive identity was expected.…”
Section: Discussionsupporting
confidence: 85%
“…A study with participants from Ghana, Kenya and South Africa indicated that higher levels of developmental assets were linked with better academic performance ( Adams et al, 2019 ). A longitudinal study with American Native Indian early adolescents indicated that developmental assets (i.e., family support, commitment to school, community and peers and personal assets (i.e., self-control) served as protective factors against risky sexual behavior (e.g., sexual debut, the number of sexual partners and condom use frequency) ( Greene et al, 2018 ). In a sample of Portuguese adolescents, a positive association was found between the number of developmental assets and the level of life satisfaction, the internal assets (particularly self-esteem in the positive identity category) having stronger association with life satisfaction than the external assets ( Soares et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with 510 students who self-identified as American Indian, Greene, Eitle, and Eitle (2018) investigated the protective role of personal, family, school, and community assets in risky sexual behaviors, such as early sexual debut, number of sexual partners and frequency of condom use. They found that selfcontrol (personal asset), family support and parent communication (family assets) as well as school attachment and non-deviant friends (school assets) and caring adults (community asset) were protective of several of the risky sexual behaviors.…”
Section: Development Assets and Risk Behaviorsmentioning
confidence: 99%
“…For example, AI youth who initiate sexual activity at young ages are three times less likely to use a condom and two times more likely to report having more than one sexual partner compared to those who initiate later [20, 21]. These behaviors place AI youth at greater risk for sexually transmitted infections (STIs) and for pregnancy [22, 23]. Assessing the ways in which residential mobility may operate in early adolescence to increase sexual risk may provide an opportunity to decrease disparities in later teen years.…”
Section: Introductionmentioning
confidence: 99%